Letture gramsciane di Giuseppe Lombardo Radice (II parte) - Pietro Maltese (Firenze University Press, 2012)
In Gramsci's intellectual development is not a place on the periphery is occupied by the figure of Lombrado Root. Prominent character of pedagogy idealism and importer in Italy, activist of instances (even American), socialist "romantic, sentimental, unscientific." Lombardo Radice was a careful student of the drama of the South and Gramsci was always very interested in the work of the Sicilian and there are many similarities (apparent) between the two intellectuals: 1) the focus on popular culture, 2) the combination between educational and political problems, and 3) the reference to the figure of Leonardo and other similarities yet. The author has done a thorough research work and significant.